Comparison of Academic Achievement of Bidikmisi and Non Bidikmisi Scholarship Awardee Students - Karmila Karmila; Ilham Thaief; Inanna Inanna; Thamrin Tahir; Muhammad Dinar (INSIGHT: Indonesian Journal Social Studies and Humanities, 2021)
This study aims to determine the comparison of academic achievement between students receiving Bidikmisi scholarships and non-Bidikmisi students in the economic education study program majoring in economics, Makassar State University. This study uses a comparative design with a quantitative approach. The population in this study was 330 students of economic education study program class 2017, 2018 and 2019 and obtained a sample of 34 Bidimisi students and 34 non Bidikmisi students. Data collection using questionnaire distribution. The analysis technique used is a comparative analysis technique. The results of this study indicate that the academic achievement of Bidikmisi students in the economic education study program majoring in economics, Makassar State University is higher than that of non Bidikmisi students, although only slightly. In using the comparison test, there is a difference in academic achievement between students receiving the Bidikmisi scholarship and non-Bidikmisi scholarship recipients, but it is not significant.